Etymological dictionary of Egyptian - Takács, Gábor. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
This is the third and final volume of the Etymological Dictionary of Egyptian . It comprises the Egyptian words with initial m-. The amount of material offered, the extensive treatment of scholarly discussions on each item, and the insights into the connections of Egyptian and the related Afro-Asiatic (Semito-Hamitic) languages, including many new lexical parallels, will make it an indispensable tool for comparative purposes and an unchallenged starting point for every linguist in the field. The reader will find the etymological entries even more detailed than those of the introductory volume, due to the full retrospective presentation of all etymologies proposed since A. Erman's time, and thanks to an extremely detailed discussion of all possible relevant data even on the less known Afro-Asiatic cognates to the Egyptian roots.